Kopi dan Kolonial: Kontribusi Afdeling Malang terhadap Ekonomi Kolonial Belanda, 1830-1930 - Moh. Heris Setiawan; Daya Negri Wijaya (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2025)
During the dutch colonial era, coffee was not just a commodity, but also a tool of power and the mainstay of the dutch east indies economy. The java region, especially the Malang Afdeling, played an important role in coffee production since the implementation of the forced cultivation system (Cultuurstelsel) in 1830. This research began with curiousity about how the role of Afdeling Malang, with all its geographical and social potential, contributed to the colonial economy for more than a century. The aims of this study is to trace the role of Afdeling Malang in the colonial coffee production and distribution network, particularly in the economic sector. as well as to see its impact on local communities at al time. The method used in this research is a historical research method from literature studies as the main technique for collecting data sources. The data sources analyzed include books, research journals, colonial archives, dutch east indies goverment document, and plantation report. From the research result, it was found that the Malang Afdeling played an important role and many local people were involved as coffee plantation workers under the strict control of the ducth goverment and businessmen. The contribution of the Malang Afdeling to the dutch east indies economy was enormous, but it was built on a structure that was unfair to the local population.